Konsep kepemimpinan guru dalam perspektif pendidikan Islam - Fuad, Rahmad; Junaidi,; Supriadi, (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
This paper aims to describe the leadership role of teachers in Islamic education. This research uses the literature study method by analyzing primary sources from books and journals. The results of the study show that leadership is a crucial element in organizations, including in education. Effective leadership is the main key in determining the success of education, especially because of the many managerial aspects that must be managed. In the Islamic perspective, the Prophet Muhammad PBUH has shown ideal leadership traits, such as honesty, trustworthiness, communicativeness and intelligence. In addition, teacher leadership in Islamic education emphasizes the importance of exemplary and good communication skills as part of leadership duties. Thus, a teacher not only acts as an educator but also as a leader who is able to provide positive examples for students. Abstrak Tulisan ini bertujuan untuk menggambarkan peran kepemimpinan guru dalam pendidikan Islam. Penelitian ini menggunakan metode studi pustaka dengan menganalisis sumber-sumber primer dari buku dan jurnal. Hasil studi menunjukkan bahwa kepemimpinan merupakan elemen krusial dalam organisasi, termasuk dalam dunia pendidikan. Kepemimpinan yang efektif menjadi kunci utama dalam menentukan keberhasilan pendidikan, terutama karena banyaknya aspek manajerial yang harus dikelola. Dalam perspektif Islam, Nabi Muhammad saw. telah menunjukkan sifat-sifat kepemimpinan yang ideal, seperti jujur, amanah, komunikatif, dan cerdas. Selain itu, kepemimpinan guru dalam pendidikan Islam menekankan pentingnya keteladanan serta keterampilan komunikasi yang baik sebagai bagian dari tugas kepemimpinan. Dengan demikian, seorang guru tidak hanya bertindak sebagai pendidik tetapi juga sebagai pemimpin yang mampu memberikan contoh positif bagi peserta didik.